The report on the 10th The International Conference on Education and Educational Psychology (ICEEPSY) - Balaban, Vlado (e-Pedagogium, 2020)
From the 9th - 12th October 2019, the 10th International Conference on Education and Educational Psychology (ICEEPSY) was presented in Barcelona, Spain. The venue was organized by Future Academy from London (UK).